Program Pembinaan Orang Tua di Sekolah Al Falah Jakarta - Parina Parina; Budi Handrianto; Anung Alhamat (Adaara: Jurnal Manajemen Pendidikan Islam, 2021)
The purpose of this study was to obtain an overview of the parental coaching program carried out at Al Falah School in Jakarta to find out the background, goals, obstacles and benefits of the parental development program at Al Falah School which is called the Program Pelatihan Guru dan Orang Tua (PPOT). The method used in this research is a case study. Cooperation between the school and parents of students is very important to achieve educational goals. The synergy of education at home and school is needed so that educational programs in schools can be continued at home or vice versa. Family education is the basis and key to further education. So that the center of education should be at home. But today the center of education is moving from home to school. Parents are not ready to become educators for their children. Al - Falah School requires parents to be involved in their children's education, not only fully surrendering education to the school. Parents must be able to be good teachers for their children because parents are the first teachers, schools help parents as second teachers. In order to increase the capacity of parents, schools require parents to take part in a training program called Program Pelatihan Guru dan Orang Tua (PPOT). PPOT in Al Falah is carried out using various methods so that it can make parents aware of being educators for their children and also make parents have skills in educating their children.